2019
DOI: 10.1038/s41556-019-0287-4
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ metabolism governs the proinflammatory senescence-associated secretome

Abstract: Cellular senescence is a stable growth arrest that is implicated in tissue ageing and cancer. Senescent cells are characterized by an upregulation of proinflammatory cytokines, which is termed the senescence-associated secretory phenotype (SASP). NAD + metabolism influences both tissue ageing and cancer. However, the role of NAD + metabolism in regulating the SASP is poorly understood. Here we show that nicotinamide phosphoribosyltransferase (NAMPT), the rate-limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
265
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 281 publications
(272 citation statements)
references
References 45 publications
6
265
0
1
Order By: Relevance
“…Retrovirus and lentivirus infection. Retrovirus production and transduction were performed using Phoenix cells to package the infection viruses (Dr. Gary Nolan, Stanford University) 26 . Lentivirus was produced using the ViraPower kit (Invitrogen) based on the manufacturer's instructions in the 293FT human embryonal kidney cell line by Lipofectamine 2000 transfection (Thermo Fisher, Cat.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Retrovirus and lentivirus infection. Retrovirus production and transduction were performed using Phoenix cells to package the infection viruses (Dr. Gary Nolan, Stanford University) 26 . Lentivirus was produced using the ViraPower kit (Invitrogen) based on the manufacturer's instructions in the 293FT human embryonal kidney cell line by Lipofectamine 2000 transfection (Thermo Fisher, Cat.…”
Section: Methodsmentioning
confidence: 99%
“…For oncogene-induced senescence, IMR90 cells were infected with retrovirus produced by pBABE-puro-H-RAS G12V (Addgene) at 37°C for 24 h. A second round of infection was performed on the same target cells. Infected cells were drug-selected using 3 μg/ml puromycin 26 . For Etoposide-induced senescence, IMR90 or OVCAR3 cells at~60-70% confluency were treated with 50 μM or 2 μM Etoposide for 48 h. The treated cells were cultured in fresh medium and harvested at day 8.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…have recently shown that SASP is controlled by NAD + metabolism. [ 48 ] Specifically, the authors showed that the salvage arm of NAD metabolism, which is controlled by the enzyme nicotinamide phosphoribosyl transferase (NAMPT) controls the proinflammatory SASP. Using an oncogene induced senescence model and LC–MS/MS assays, the authors showed that the senescent cells have significantly increased levels of NAD+, and NAMPT mediated synthesis of NAD + (using cells with NAMPT inhibition), and was required for the secretion of SASP factors (IL‐10 and TNF‐α).…”
Section: Application Of Metabolomics For Biomarker Discovery In Agingmentioning
confidence: 99%